PERUBAHAN NILAI SOSIAL PADA PERANTAU (Studi Kasus: Masyarakat Desa Tanjungsukur Kecamatan Rajadesa Kabupaten Ciamis Yang Merantau Di Jakarta) - Ismatullah, Yolla Rachmaan; Fatgehipon, Abdul Harif (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2018)
This reseach purpose to: (1) know the behavioral changes in the village community Tanjungsukur Village District Rajadesa Ciamis Regency. (2) to know the cause factor of the social value dissolution at community resident of Tanjungsukur Village, District of Rajadesa Regency of Ciamis. This research was conducted in two places, namely in Billy Moon Housing, East Jakarta and the origin of migrants in Tanjungsukur Village. The methodology used is qualitative approach with case study method, data collection technique is done by interview, observation, field note, literature study, and documentation. The method used in data analysis is data reduction, data presentation and conclusion. Based on the results of this study it is known that: (1) behavioral changes that occur in the immigrants such as waning obedience in worship, being indifferent to the surrounding environment, loss of norms of decency and began to arise the nature of individualism. The impact of such behavioral changes such as the decrease of religious values, loss of solidarity, the emergence of a sense of egoism to cause division or conflict between members of the community. (2) factors causing the dissolution of social values caused by internal and external factors. Internal factors are due to a sense of curiosity in trying new things and a sense of mistrust, while external factors are the result of a supportive social environment, peer relationships, lack of social control, especially the family and the last low education.